Beta-Aminobutyric acid-induced resistance against downy mildew in grapevine acts through the potentiation of callose formation and jasmonic acid signaling - Hamiduzzaman, Mollah Md; Jakab, Gabor; Barnavon, Laurent; Neuhaus, Jean-Marc; Mauch-Mani, Brigitte (My University, 2005)
P-Aminobutyric acid (BABA) was used to induce resistance in grapevine (Vitis vinifera) against downy mildew (Plasmo-para viticola). This led to a strong reduction of mycelial growth and sporulation in the susceptible cv. Chasselas. Comparing different inducers, the best protection was achieved with BABA followed by jasmonic acid (JA), whereas benzo (1,2,3)-thiadiazole-7-carbothionic acid-S-methyl ester (a salicylic acid [SA] analog) and abscisic acid (ABA) treatment did not increase the resistance significantly. Marker genes for the SA and JA pathways showed potentiated expression patterns in BABA-treated plants following infection. The callose synthesis inhibitor 2-deoxy-D-glucose partially suppressed BABA- and JA-induced resistance against P viticola in Chasselas. Application of the phenylalanine ammonia lyase inhibitor 2-aminoindan-2-phosphonic acid and the lipoxygenase (LOX) inhibitor 5, 8, 11, 14-eicosatetraynoic acid (ETYA) also led to a reduction of BABA-induced resistance (BABA-IR), suggesting that callose deposition as well as defense mechanisms depending on phenylpropanoids and the JA pathways all contribute to BABA-IR. The similar phenotype of BABA- and JA-induced resistance, the potentiated expression pattern of JA-regulated genes (LOX-9 and PR-4) following BABA treatment, and the suppression of BABA-IR with ETYA suggest an involvement of the JA pathway in BABA-IR of grapevine leading to a primed deposition of callose and lignin around the infection sites.
Keywords: oomycete; SYSTEMIC ACQUIRED-RESISTANCE; VITIS-VINIFERA L; PLASMOPARA-VITICOLA; METHYL JASMONATE; TOBACCO CELLS; PERONOSPORA-PARASITICA; DL-3-AMINOBUTYRIC ACID; PHYTOPHTHORA-INFESTANS; ARABIDOPSIS-THALIANA; DEFENSE RESPONSES